Basin problem for Hénon-like attractors in arbitrary dimensions - Horita, Vanderlei [UNESP]; Muniz, Nlvaldo (My University, 2006)
We prove that Hénon-like strange attractors of diffeomorphisms in any dimensions, such as considered in [2],[7], and [9] support a unique Sinai-Ruelle-Bowen (SRB) measure and have the no-hole property: Lebesgue almost every point in the basin of attraction is generic for the SRB measure. This extends two-dimensional results of Benedicks-Young [4] and Benedicks-Viana [3], respectively.
Keywords: Hénon-like attractor; Non-uniformly hyperbolic system; SRB measure